Reliability of ZigBee transmission in agriculture production - I. Mašík (Research in Agricultural Engineering, 2013)
Currently, the unlicensed ISM (Industrial Scientific and Medical) band 2.4 GHz has become saturated due many standards used at once. In agricultural production ZigBee has a lot of applications, from wireless sensors networks to complicated automation applications. This paper deals with improving the coexistence properties of ZigBee (IEEE 802.15.4), while keeping compatibility with the basic standard. This paper describes principles and application of forward error correction above the physical layer, consisting of block data interleaver and Hamming code, and also the effect of improvements in coexistence with variously loaded WiFi 802.11g.